Roman Myth and Ritual: Groups of Luperci and Epigraphic Evidence - Vukovic, K (Università di Bologna, 2016)
The Lupercalia was one of the most popular and ancient festivals in Roman religion. On the 15th February young men would strip to their loincloths and run around the Palatine playfully striking those they met with skins of a he-goat.